Carbon with Surface‐Enriched Nitrogen and Sulfur Supported Au Catalysts for Acetylene Hydrochlorination. Issue 3 (15th January 2019) - Wang, Bolin; Zhao, Jia; Yue, Yuxue; Sheng, Gangfeng; Lai, Huixia; Rui, Jiayao; He, Haihua; Hu, Zhong‐ting; Feng, Feng; Zhang, Qunfeng; Guo, Lingling; Li, Xiaonian
Abstract: Nitrogen‐doped carbons supported gold catalysts has attracted much attention in a broad range of applications. However, co‐existence of multiple nitrogen species which may have vastly different effect on the gold‐based catalysts, has limited the development of an ideal nitrogen‐doped carbon support. Herein, we have demonstrated that by addition of sulfur species, selective formation of pyrrolic nitrogen against pyridinic nitrogen can be achieved for pyrrolic nitrogen doped carbon support. The gold catalysts synthesized from the pyrrolic nitrogen doped carbon support produced using ionic liquid‐assisted synthetic strategy (Au/N, S‐AC‐700), exhibited excellent catalytic activity and stability for hydrochlorination of acetylene. The outstanding performance was attributed to the π electrons transferred from pyrrolic nitrogen to Au (III) center, which could increase the electron density of Au hence facilitate the adsorption of hydrogen chloride on the catalyst. Abstract : Green economy ? Carbon with surface‐enriched nitrogen and sulfur supported Au catalysts was developed for acetylene hydrochlorination . The presence of sulfur species on the carbon surface inhibited the formation of pyridinic N which was not necessary for the hydrochlorination of acetylene.